THE EFFECT OF SALARY AND WORK INSURANCE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MEDIATION VARIABLE IN A STUDY AT PT PATRIOT INTAN ABADI - Nopal Pahlawan; Muh Abdul Aziz; Nurni Arrina Lestari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
In an era of increasingly competitive business competition, employee performance is a key factor in organizational success because it plays a direct role in achieving company goals and sustainability. One effort that companies can make to improve employee performance is through compensation management, especially salary and work insurance, by paying attention to the level of employee job satisfaction. This study aims to analyze the effect of salary and work insurance on employee performance with job satisfaction as a mediating variable at PT Patriot Intan Abadi. This study uses a quantitative approach with a causal design. Data were obtained through a survey using questionnaires distributed to all employees of PT Patriot Intan Abadi involved in the chicken farming project. The study population was 120 employees and all of them were used as research samples. The data analysis technique used Structural Equation Modeling (SEM) with the help of AMOS 26.00 software. The results of the study indicate that salary has a positive and significant effect on employee job satisfaction (estimate = 0.208; p-value = 0.019), and work insurance has a positive and significant effect on employee job satisfaction (estimate = 0.353; p-value 0.000). Job satisfaction is also proven to have a positive and significant effect on employee performance (estimate = 0.245; p-value = 0.015). However, salary does not have a significant direct effect on employee performance (estimate = 0.139; p-value = 0.107), while work insurance has a positive and significant effect on employee performance (estimate = 0.391; p-value 0.000). These findings indicate that job satisfaction acts as a full mediating variable in the relationship between salary and employee performance, as well as a partial mediating variable in the relationship between work insurance and employee performance.